Analysis of Subject-Verb Agreement Errors in Third Person Singular Verb Forms by Spanish University Students: A Corpus-Based Study - López Pérez, Sidoní (International Journal of English Linguistics, 2025)
This study is aimed at analyzing subject-verb agreement (SVA) errors with third person singular lexical verbs in the Present Simple by Spanish higher-education students in a computerized learner corpus from Universidad Internacional de La Rioja (UNIR). The corpus is composed of 155 participants and 246 writing samples and it consists of the students’ spontaneous writings in response to a compulsory online forum from the nonlinguistic subject, ICT Tools Applied to the Learning of English, which is included in the curriculum of the Degree in Early Years Education. The SVA errors found in the corpus were classified according to Dulay, Burt and Krashen’s (1982) Surface Strategy Taxonomy, which groups language errors into four different types: omission, addition, misformation and misordering. The results show that the most frequent type of error made by the students is misformation, followed by misordering and by addition, which account for almost 95% of the total number of errors, whereas omission is the least frequent type of error, accounting for only 5% of all the errors. At the same time, the analysis indicates that the errors produced by the students are mainly intralingual, reflecting an inadequate or incomplete learning of the target language, and also interlingual since some errors committed by the learners are related to native language (NL) transfer. These results suggest some pedagogical implications for the teaching and learning of SVA rules which are also included in the paper.
Keywords: subject-verb agreement; present simple; 3rd person singular verb forms; Surface Strategy Taxonomy; intralingual; interlingual